PERANAN HUBUNGAN MASYARAKAT DALAM MEMBANGUN CITRA PERUSAHAAN PADA PT PEGADAIAN (PERSERO) KANWIL I MEDAN - Agnita Yolanda; Nurismilida Nurismilida; Lely Khairuna (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2017)
The authors are interested in conducting research with the title role of public relations in building the image of the company at PT Pegadaian (Persero) Kanwil I Medan. The researcher used quantitative methods. The results of research that the author achieve on PT Pegadaian (Persero) Kanwil I Medan is to have a PR section that plays an important role in building corporate image with the average value sorted from the highest data IE facilitator indicators of troubleshooting process (3.33), communication facilitators (3.29), expert advisor (3.28), communication technician (3.27). So the author's advice to the company is to continue to improve the positive corporate image by building a better communication with internal and external parties of the company and should further improve the communication technician by making the product or communication activities become more effective.Keywords: Public Relations, Corporate Image, PT Pegadaian